Development strategy of home industry golla kambu in Lagi-Agi Village, Campalagian Subdistrict, Polewali Mandar Regency - Mardiana, Mardiana; Khaeratih, Rahma; Sulili, Anwar; Arhim, Muhammad (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2020)
Home industry in Polewali Mandar Regency in 2014 reached 6,035 industries. The number of micro and small businesses increased 1.34 percent. The workforce involved in micro and small industries reached 13,470 people. Polewali Mandar main area which incidentally has a Mandar tribe has some special culinary. One of them is Golla Kambu or what is commonly called Wajik Lokal Mandar. These local Mandar food entrepreneurs adjust the market because it has become a typical local snack. In fact, now Golla Kambu has been eyeing foreign tourists when they travel in West Sulawesi. Along the road in Lagi-Agi Village, Campalagian Subdistrict precisely Polewali Mandar, many of the Mandar local food are often found. Along the way we will find many stalls that provide this food with different prices and flavors. One of the other advantages of this food is that it is durable, even though it does not use preservatives, Golla Kambu can last for months using only a wrapper of dried banana leaves. To make Golla Kambu is actually very simple, practical and the material is easy to obtain. The basic ingredients are only three, namely selected glutinous rice, palm sugar and young grated coconut. Three main ingredients are mixed into one, put in a suitable bowl or place and then cooked for several hours to form a good mixture. The end result is then wrapped in dried banana leaves in a small size. Besides its simple taste, the price is quite affordable for visitors. The famous Golla Kambu in Mandar comes from the area of Lagi-Agi Village, Campalagian Subdistrict, Polewali Mandar Regency.